MINERALOGY, GEOCHEMISTRY AND RADIOACTIVITY OF THE URANIUM MINERALIZATION AND DETERMINATION OF LITHOLOGICAL CHARACTERIZATION IN THE DADAGI TOWN, CENTRAL ANATOLIAN, TURKEY - Alcicek, Omer Nedim; Kalender, Leyla (Stef92 Technology Ltd, 2015)
The granitic bodies that are named as Central Anatolian Crystalline Complex (CACC) which are used for deep under ground facilities, such as a uranium storage facility in the Eocene sedimentary units at Dadagi inTurkey. Include in this study was performed both chemical analysis and radiometric measurement and interpreted to source of uranium. Major oxide and U relationship indicated that enrichments of U are high in the silts. Al2O3, Fe2O3 and P2O5 contents are high at the silts samples due to clay minerals and organic matters. Distribution of trace elements (U, Th, Ba, Cs, Ga, Hf, Nb, Rb, V, Zr, W, Y, Mo, Cu, Zn, Ni, As, Sb, Bi, Ag, Au, Hg and Tl) in the silts are more than siliceous limetones. In addition to between U and V, W, Zr and Y relationships are high positive due to Idis granitic rocks form CACC. Between U and Ba, Cu, Zn, As, Sb, Bi, Ag, Au are high positive corelation due to same originate from hydothermal fulids. The heavy REEs (Eu-Lu) concentrations are high (>1) in both studied lithological units (siliceous limestone and silts). The mineralogical studies indicated that the uranium carbonate minerals are enriched in calcite filling fracture in the silicious limestone in alkalin environment as linking to fault zone. The more uranium enrichments are observed within the studied silts due to adsorbed or ion exchanged on the finer grain fraction by clay minerals form hydrothermal solutions. The used of D-factor determination of equilibrium state of the studied rocks were chemically analyzed uranium greater than the radiometrically determined uranium reflecting a disequilibrium state characterized by addition of uranium. The origin of uranium mineralization is mainly related to alteration of primary minerals by the action of oxidizing/reducing fluids, then redeposition in other forms. Redistribution by circulating origin of meteoric hydrothermal waters and ground water might have taken important role. The utilization of fault/fracture zones and clay-rich horizons at the lake sediments in the Ayhan Lacustrin basin may prove useful in the search for U resources.
15th International Multidisciplinary Scientific Geoconference (SGEM) -- JUN 18-24, 2015 -- Albena, BULGARIA
Keywords: Geochemistry; Nevsehir; Dadagi; Uranium